Educational Transformation in Indonesia: Pedagogical and Cybergogy Orientation in the Age of Artificial Intelligence for English Subjects at Islamic Boarding School - Efrizal, Dedi; Badeni, Badeni; Kristiawan, Muhammad; Risdianto, Eko; Febriani, Hanura (Linguists : Journal of Linguistics and Language Teaching, 2024)
This study aimed to explore the optimal and efficient pedagogical and cybergogy transformation for both teachers and students in the era of artificial intelligence (AI) in English subjects at Madrasah Aliyah of Darussalam Modern Islamic Boarding School, Kepahiang, Bengkulu since the use of AI in English subject at Islamic boarding schools has been notably inadequate due to many primary concerns. The restricted technological infrastructure includes inadequate internet connectivity and insufficient access to AI gear and software. By examining the dynamics within the school, the study seeks to empower students to enhance their critical thinking, reflection, creativity, and productivity in the digital-based education era. This study used a qualitative descriptive approach, the researchers collected data through visual observation and interviews with the English teachers and students. In analyzing the data, the researchers used the interactive model of triangulation data that developed by Miles and Hubermann. The study's findings reveal several key elements for the effective implementation of pedagogical and cybergogy transformations. First, customization of learning is essential. With AI, teachers can personalize instructional materials and methods to meet individual students' needs, skill levels, and learning styles. Interactive technologies are also critical, as they increase student engagement and foster collaborative online learning. AI technology provides quick feedback and automates assessments, streamlining the evaluation process. Additionally, AI can be used to source and deliver authentic educational materials, such as news articles, podcasts, or videos, aligned with students' competence levels. Beyond improving language proficiency, AI helps develop students' critical thinking, creativity, and problem-solving skills. To fully leverage AI, teachers must also enhance their digital competencies, enabling them to integrate AI effectively into their teaching and guide students in using these technologies responsibly and ethically.